Analysis of images, social networks and texts : 7th International Conference, AIST 2018, Moscow, Russia, July 5-7, 2018, Revised selected papers /: 7th International Conference, AIST 2018, Moscow, Russia, July 5-7, 2018, Revised selected papers. (2018) - Unknown
No abstract available